Pesona Objek Wisata Sejarah di Kabupaten Sinjai - Wahyudi Ishak; Ahmadin; Najamuddin (Politeknik Pariwisata Makassar, Indonesia, 2020)
This study aims to determine the potential of historical attractions in Sinjai Regency, the development of historical tourism in Sinjai Regency 2008-2016, and the impact of historical tourism on the communities around the site, the government and tourists. The method used in the research and writing of this thesis is a historical research method, which includes: heuristics, source criticism, interpretation and historiography. The techniques used in data collection are observation, interview and literature study techniques. The results of this study indicate that Sinjai as a Level II Region in South Sulawesi has tourism potential that is not inferior to other regions. The Batupake Gojeng Archaeological Park, the Karampuang Indigenous Area, and the Balangnipa Fort are one of the historical tourist destinations offered by Sinjai Regency. Although the Tourism and Culture Office of Sinjai Regency was only established in 2017, activities in the tourism sector will continue to be carried out in previous years. The three historical attractions have their respective developments both in terms of facilities and infrastructure to the number of visitors. The contribution of each element in the development of the historical tourism sector in Sinjai Regency is something that needs to be improved. Based on the results of this study it can be concluded that the historical attractions in Sinjai Regency have an impact on the socio-cultural, educational and economic sectors for the local government and the people who live around the site.